1972
DOI: 10.1021/jo00984a018
|View full text |Cite
|
Sign up to set email alerts
|

Rates of electrocyclic reactions. Conversion of .alpha.-pyrans to cis-dienones

Abstract: The equilibrium constant, Kw = 0.094, for the interconversion of l-oxa-2,5,5,8a-tetramethyl-5,6,7,8-tetrahydronaphthalene (3) and c¿s-/3-ionone (2) was measured at several temperatures, AH°= 5.5 keal/mol and 5°= 14 eu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Thus, acceleration of cyclobutene electrocyclizations by 3,4-substitution (e.g., Stephenson and Brauman, 1974) can be considered to result from increased σ-π* and σ*-7τ mixing, or by stabilization of the partial radical centers resulting in the transition state of σ bond breaking. Furthermore, such interactions can also be invoked to explain the much more facile electrocyclization of dienones to 2/f-pyrans as compared to the corresponding triene to cyclohexadiene interconversions (Marvell et al, 1972). For example, oxetenes under go electrocyclization to a,0-unsaturated ketones 107 faster than the analogous cyclobutenes (Friedrich and Schuster, 1971).…”
Section: Reactivitymentioning
confidence: 99%
“…Thus, acceleration of cyclobutene electrocyclizations by 3,4-substitution (e.g., Stephenson and Brauman, 1974) can be considered to result from increased σ-π* and σ*-7τ mixing, or by stabilization of the partial radical centers resulting in the transition state of σ bond breaking. Furthermore, such interactions can also be invoked to explain the much more facile electrocyclization of dienones to 2/f-pyrans as compared to the corresponding triene to cyclohexadiene interconversions (Marvell et al, 1972). For example, oxetenes under go electrocyclization to a,0-unsaturated ketones 107 faster than the analogous cyclobutenes (Friedrich and Schuster, 1971).…”
Section: Reactivitymentioning
confidence: 99%
“…It has been shown that 1,2-pyrans exist mainly in the oxodiene form and that substituents capable of enhancing the resonance in this isomer also displace the equilibrium in its favor (2)(3)(4)(5). The formation of a-pyrones was thought at first to proceed through the pyrilium salt because of the ease with which 5,5-dimethoxy-2-n-decylpenta-2,4-dienal (1) was converted to such a compound and since the intermediate 1,2-pyrans (orthoesters) were expected to be stable in basic media.…”
Section: With 0-methoxy Enonesmentioning
confidence: 99%
“…The strong influence of the kind of 2,3-anellation in 2H-pyrans on the tendency of an electrocyclic ring opening reaction is shown by a comparison with the known 2,5,5,8a-tetramethyl-6,7,8,8a-tetrahydro-5H-chromene [9]. An equilibrium between the two isomers can be observed, since in this case the resulting acyclic valence isomer contains the Financial support by the Fonds der Chemischen Industrie is gratefully appreciated.…”
mentioning
confidence: 97%